2022
DOI: 10.3390/cells11162526
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Does Not Possess Intrinsic Superantigen-like Inflammatory Activity

Abstract: Multisystem inflammatory syndrome in children (MIS-C) is a rare hyperinflammatory disease occurring several weeks after SARS-CoV-2 infection. The clinical similarities between MIS-C and the toxic shock syndrome, together with the preferential expansion of T cells with a T-cell receptor variable β chain (TCRVβ) skewing, suggested a superantigen theory of MIS-C. For instance, recent in silico modelling evidenced the presence of a highly conserved motif within SARS-CoV-2 spike protein similar in structure to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…To verify the functional relevance of our computational simulations, we performed a kinetic analysis of inflammatory cytokine secretion in culture supernatants of highly purified (> 95%) primary CD4 + T cells ( Supplementary Figures S1A, B ) stimulated with SEB alone. Consistently with our previous data ( 27 , 43 ), CD4 + T cells isolated from the peripheral blood of healthy donors (HD) expressed CD28 (mean ± SEM = 96.37 ± 2.41) but neither HLA-DR (mean ± SEM = 3.1 ± 0.9) nor B7.1/CD80 (mean ± SEM = 0.98 ± 0.59) nor B7.2/CD86 (mean ± SEM = 1.81 ± 0.88). Stimulation of CD4 + T cells with SEB alone induced a strong production of IFN-γ ( Figure 3A ), IL-2 ( Figure 3B ), IL-6 ( Figure 3C ), TNF-α ( Figure 3D ), IL-17A ( Figure 3E ), IL-22 ( Figure 3F ) and GM-CSF ( Figure 3G ) after 48-72 hours.…”
Section: Resultssupporting
confidence: 94%
“…To verify the functional relevance of our computational simulations, we performed a kinetic analysis of inflammatory cytokine secretion in culture supernatants of highly purified (> 95%) primary CD4 + T cells ( Supplementary Figures S1A, B ) stimulated with SEB alone. Consistently with our previous data ( 27 , 43 ), CD4 + T cells isolated from the peripheral blood of healthy donors (HD) expressed CD28 (mean ± SEM = 96.37 ± 2.41) but neither HLA-DR (mean ± SEM = 3.1 ± 0.9) nor B7.1/CD80 (mean ± SEM = 0.98 ± 0.59) nor B7.2/CD86 (mean ± SEM = 1.81 ± 0.88). Stimulation of CD4 + T cells with SEB alone induced a strong production of IFN-γ ( Figure 3A ), IL-2 ( Figure 3B ), IL-6 ( Figure 3C ), TNF-α ( Figure 3D ), IL-17A ( Figure 3E ), IL-22 ( Figure 3F ) and GM-CSF ( Figure 3G ) after 48-72 hours.…”
Section: Resultssupporting
confidence: 94%
“…The Wuhan Hu-1 sequences of these epitopes contain ‘PRRA’, which is a motif forming a core of a hypothesised and controversial SARS-CoV-2 ‘superantigen’ [ 26 , 27 ]. This so-called ‘SARS-CoV-2 superantigen’ has been hypothesised to play a role in post-COVID-19 multisystem inflammatory syndrome [ 20 , 23 ], although a recent study found no evidence for its ‘intrinsic superantigen-like inflammatory activity’ [ 36 , 37 ]. In fact, 9/15 (60%) pMHC-I containing this hypothesised superantigen core are predicted to become ‘nonbinders’ as a result of BA.1 mutation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This superantigen effect of Spike could explain “ multi-system inflammatory syndrome ” (MIS-C) in children/adolescents after COVID-19, a phenomenon observed also after COVID-19 vaccines [ 155 , 156 , 157 , 158 , 159 ]. However, a recent paper demonstrated that Spike is not able to act as a superantigen in human cell lines in vitro [ 160 ]. It will be interesting to ascertain the effect of smaller parts of the Spike protein in regard to their possible cytotoxic effect to understand what is causing such high inflammation.…”
Section: Possible Mechanisms Of Covid-19 Mrna Vaccine-induced Tissue/...mentioning
confidence: 99%